2017
DOI: 10.1136/jclinpath-2017-204355
|View full text |Cite
|
Sign up to set email alerts
|

Increased alloimmunisation and transfusion reaction reporting in patients with solid-phase panreactivity

Abstract: Our data suggest that patients with SPP have higher rates of reported transfusion reactions and alloantibody development compared with those without SPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Recently, solid-phase unidentified reactions have been associated with female sex or diagnoses like cancer, pregnancy, surgery, and trauma, and data gathered in our patients are in line with these observations [24]. Although it has been recently reported that a minority of patients with nonspecific reactivity at SPRCA might develop new auto- or alloantibodies, the majority of them tend to become definitely negative at following alloantibody screenings, thus confirming the elusive nature of these results [24,25]. In our scenario, however, consisting in patients at very low transfusion risk, the false-positive results could require additional investigations finally resulting in the delay of surgical procedures.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, solid-phase unidentified reactions have been associated with female sex or diagnoses like cancer, pregnancy, surgery, and trauma, and data gathered in our patients are in line with these observations [24]. Although it has been recently reported that a minority of patients with nonspecific reactivity at SPRCA might develop new auto- or alloantibodies, the majority of them tend to become definitely negative at following alloantibody screenings, thus confirming the elusive nature of these results [24,25]. In our scenario, however, consisting in patients at very low transfusion risk, the false-positive results could require additional investigations finally resulting in the delay of surgical procedures.…”
Section: Discussionsupporting
confidence: 86%
“…A similar phenomenon of panreactive SPRCA accompanied by a negative autocontrol and a lack of specificity but later acquired alloantibodies was described by Olofson et al, suggesting higher rates of both transfusion reactions and alloantibody development at 2% and 11%, respectively, compared to those without SPRCA panreactivity [17]. Liu et al reported approximately 18% of the gel‐based antibody screens as AUS.…”
Section: Discussionsupporting
confidence: 52%
“…[4][5][6] One pattern of such reactivity is panagglutination, although the exact mechanism for this phenomenon remains unclear. 3,7,8 In addition, SPRCA assays appear to be more sensitive for the detection of warmreactive autoantibodies than other primary antibody detection methods. 4,6 In a previous study of NSP antibodies, the authors identified an interesting pattern of reactivity: panreactive SPRCA plasma testing with a negative PEG-tube test and a negative DAT.…”
Section: Discussionmentioning
confidence: 99%